36=(x-9)(x)
multiply out the brackets gives
36=x^2-9x
set it equal to zero
x^2-9x-36=0
factor it back into brackets
(x+3)(x-12)=0
so either (x+3)=0 or (x-12)=0
so x is either -3 or else it's 12
2007-01-03 13:00:45
·
answer #1
·
answered by adriantheace 4
·
0⤊
0⤋
x = 12 is one answer; the other one is x = -3.
To solve this, first expand the product on the right hand side. Then put it in the standard quadratic form and factorise it.
36 = (x-9)(x)
=> 36 = x.x - 9.x
=> x^2 - 9x - 36 = 0
=> (x - 12) (x + 3) = 0
=> x - 12 = 0 or x + 3 = 0
=> x = 12 or -3.
If you can't factorise the equation, there is a formula:
if ax^2 + bx + c = 0
then x = (-b +/- sqrt(b^2 - 4ac)) / (2a)
assuming that b^2 - 4ac >= 0 (if this is negative there are no [real] solutions; there are what are called complex solutions, but that's a way off from where you are yet.)
Here 1.x^2 + (-9).x + (-36) = 0
so a = 1, b = -9, c = -36.
So the answers are
x = [-(-9) +/- sqrt((-9)^2 - 4.1.(-36))] / (2.1)
= [9 +/- sqrt(81 + 144)] / 2
= (9 +/- sqrt(225)) / 2
= (9 +/- 15) / 2
= 24/2 or -6/2
= 12 or -3.
2007-01-03 12:27:36
·
answer #2
·
answered by Scarlet Manuka 7
·
0⤊
0⤋
2x+9=31 2x+9 -9 =31-9 2X=22 2x/2= 22/2 x-11 5x-7=38 5x-7+7=38+7 5x=40 5 5x/5=40 5/5 x=9 12-x=21 12=21+x 21-12=x x=9 ...the rest you're able to do on ur very own, merely stick to my occasion, or you will not discover out a thank you to do it precise and could do undesirable in an prolonged time =]
2016-10-19 10:33:19
·
answer #3
·
answered by johannah 4
·
0⤊
0⤋
36=(x-9)(x
36=x^2-9x (distributive property)
x^2-9x-36=0(subtract 36)
2 numbers that multiply to -36 and add up to -9
-12 and 3
(x-12)(x+3)
x= 12 and -3
-3 is not needed if you are trying to find a length of something.
2007-01-03 12:27:19
·
answer #4
·
answered by 7
·
0⤊
0⤋
36 = (x - 9) * (x)
36 = x^2 - 9x
0 = x^2 - 9x -36
which is the same as:
x^2 - 9x -36 = 0
now you factor this into
(x + 3) * (x - 12) = 0
and so the answer is 12 and -3
2007-01-03 12:29:41
·
answer #5
·
answered by b0b 7h3 l337 2
·
0⤊
0⤋
36 = x^2 - 9x
x^2 -9x -36 = 0
(x-12)(x+3)=0
x=12 or x=-3
2007-01-03 12:27:25
·
answer #6
·
answered by Johnny Handsome 2
·
0⤊
0⤋
36=(x-9)(x)
36=x^2-9x
x^2-9x-36=0
(x-12)(x+3)=0
x-12=0, x=12
x+3=0, x=-3
{x:x=-3 and 12}
2007-01-03 12:29:14
·
answer #7
·
answered by aficionado210 2
·
0⤊
0⤋
36=(x-9)(x)
36=x(squared)-9x
square root sign on both sides of the equation
6=x-3x
6=-2x
divide by -2
answer=-3 but 12 would work too...i guess...how'd you get 12?
2007-01-03 12:32:53
·
answer #8
·
answered by lilchen94 1
·
0⤊
0⤋
i hope your not cheating on your homework...but its: (xx = squared)
x(x-9) = 36
xx - 9x = 36
and if you need it further then...
xx/9 - x = 4
it kant really get any further...
2007-01-03 12:29:13
·
answer #9
·
answered by lovin' it 2
·
0⤊
0⤋
What does the directions say?
2007-01-03 12:28:35
·
answer #10
·
answered by YaYa 3
·
0⤊
0⤋